Impact of High-standard Farmland Construction policy on labor substitution by machinery in China:Evidence from quasi-experimental approaches at the macro and micro levels - YANG Yu, XIE Zhiwen, ZHANG Lijuan, ZHANG Qian (Ziyuan Kexue)
[Objective] High-standard Farmland Construction (HSFC) policy, as an important practice of implementing the “storing grain in the land and technology” strategy, is one of the important ways to break the dilemma of high labor costs in rural areas and low mechanization level. Assessing its impact on the substitution of labor by machinery has important practical significance and theoretical values. [Methods] Rooted in the induced technological changes theory, this study employed the difference-in-differences (DID) method to assess the impact of HSFC policy on labor substitution by machinery under the condition of rising labor costs using provincial panel data (2005-2021) and household survey data of two periods from three counties in Jiangxi Province. [Results] (1) In the backdrop of selective labor transfer and rising prices, farmers increasingly favored labor substitution by machinery. (2) HSFC policy enhanced effects on labor substitution by machinery. (3) Pronounced effects of HSFC policy were observed in grain-producing areas, regions with significant labor outflows, and among large-scale farmers. (4) The HSFC policy, through measures like reducing sloping land and improving rural infrastructure, effectively enhanced labor substitution efficiency. [Conclusion] To enhance the effect of labor substitution by machinery from the HSFC policy, precise measures are required to comprehensively solidify the foundation of food security. Enhancing integrated management of sloping farmland, improving rural roads, and reducing land fragmentation are essential measures for achieving agricultural mechanization. This effort strengthens the material foundation for storing grain in the land and storing grain through technology.